Steady state fluorescence studies of wild type recombinant cinnamoyl CoA reductase (Ll-CCRH1) and its active site mutants - Sonawane, Prashant; Vishwakarma, Rishi Kishore; Singh, Somesh; Gaikwad, Sushama M.; Khan, Bashir Mohammad (Journal of Fluorescence, 2014)
Fluorescence quenching and time resolved fluorescence studies of wild type recombinant cinnamoyl CoA reductase (Ll-CCRH1), a multitryptophan protein from Leucaena leucocephala and 10 different active site mutants were carried out to investigate tryptophan environment. The enzyme showed highest affinity for feruloyl CoA (K (a) = 3.72 x 10(5) M-1) over other CoA esters and cinnamaldehydes, as determined by fluorescence spectroscopy. Quenching of the fluorescence by acrylamide for wild type and active site mutants was collisional with almost 100 % of the tryptophan fluorescence accessible under native condition and remained same after denaturation of protein with 6 M GdnHCl. In wild type Ll-CCRH1, the extent of quenching achieved with iodide (f (a) = 1.0) was significantly higher than cesium ions (f (a) = 0.33) suggesting more density of positive charge around surface of trp conformers under native conditions. Denaturation of wild type protein with 6 M GdnHCl led to significant increase in the quenching with cesium (f (a) = 0.54), whereas quenching with iodide ion was decreased (f (a) = 0.78), indicating reorientation of charge density around trp from positive to negative and heterogeneity in trp environment. The Stern-Volmer plots for wild type and mutants Ll-CCRH1 under native and denatured conditions, with cesium ion yielded biphasic quenching profiles. The extent of quenching for cesium and iodide ions under native and denatured conditions observed in active site mutants was significantly different from wild type Ll-CCRH1 under the same conditions. Thus, single substitution type mutations of active site residues showed heterogeneity in tryptophan microenvironment and differential degree of conformation of protein under native or denatured conditions.
Keywords: Active site mutants; Cinnamoyl CoA reductase; fluorescence; Ligand binding; Solute quenching